Designing new Togni reagents by computation. Issue 39 (29th April 2019) - Jiang, Heming; Sun, Tian-Yu; Chen, Ying; Zhang, Xinhao; Wu, Yun-Dong; Xie, Yaoming; Schaefer, Henry F.
Abstract : New trifluoromethylating reagents are designed based on trans influence and steric effect. Abstract : New trifluoromethylating reagents are designed via computational studies inspired by Togni's experimental research. Trans influence and steric effects are important for this rational design. We have found that the Togni derivative with X = SO2 is the best choice based on its high reactivity and its potential synthesis.